(3GdWQjb Gdi GMJQGa (BSQL SERVER /s - (3YHO GdfHj, gGfjs; (3YRH, YRH eMeOs ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B, s, 2004)
(3ebOeI Yf bhGYO GdHjGfGJ(B- (3LedI (BDATA SELECT- (3GSJNOeGJ eJbOeI ddCeQ(BSELECT- (3GfTGA YfGUQ bGYOI GdHjGfGJ(B- (3GdJYGed eY GdHjGfGJ(B- (3GfTGA YfGUQ HjGfGJ CNQi(B- (3GdJMce aj UdGMjGJ GdeSJNOejf(B- (3GdELQGAGJ GdCMOGK(B- (3JWHjb Ydi bGYOI GdHjGfGJ (BSQL(3HGSJNOGe (Bvisual basic .s
Keywords: (3GdEYdGe GdCdjs; (3GdHQeLjGJs; (3GdMGShHs; SQL SERVER